PENGARUH PERSEPSI GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR: PERAN KOMITMEN ORGANISASIONAL SEBAGAI PEMEDIASI (SURVEY PADA KARYAWAN BPR DI WILAYAH SURAKARTA) - Rohwiyati .; Praptiestrini . (Universitas Sahid Surakarta, 2019)
This study aims to analyze (1) effect perceptions of transformational leadership and job satisfaction on organizational commitment, (2) effect perceptions of transformational leadership, job satisfaction, and organizational commitment on organizational citizenship behavior, (3) effect perceptions of transformational leadership and job satisfaction on organizational citizenship behavior through organizational commitment. Samples on this research of 103 BPR employees in the Surakarta region. Data analysis using path analysis. Conclusions (1) transformational leadership perceptions and job satisfaction have a significant effect on organizational commitment, (2) transformational leadership perceptions, job satisfaction, and organizational commitment have significant effect on organizational citizenship behavior, (3) organizational commitment mediate the effect perceptions of transformational leadership and job satisfaction on organizational citizenship behavior.